Instrumented nanoindentation and scanning electron transmission microscopy applied to the study of the adhesion of InP membranes heteroepitaxially bonded to Si. Issue 2 (14th February 2014) - Pantzas, Konstantinos; Le Bourhis, Eric; Patriarche, Gilles; Itawi, Ahmad; Beaudoin, Grégoire; Sagnes, Isabelle; Talneau, Anne
<x content-type="archive" xml:space="preserve">Abstract</x> Instrumented nanoindentation and STEM have been combined ex situ to study the adhesion of 450 nm thick InP membranes to Si substrates. Three distinct regimes are identified in the deformation of the InP/Si stacks during these experiments: the first is plastic flow of InP at low loads; the second is elastic debonding of the InP membrane, far from the indented zone at medium loads; lastly, the local amorphisation of the underlying Si substrate at high loads. The regime of intermediate loads is shown to be particularly useful in the evaluation of the surface bonding energy of InP to Si.